2016
DOI: 10.1080/02699931.2016.1225004
|View full text |Cite
|
Sign up to set email alerts
|

Toward an implicit measure of emotions: ratings of abstract images reveal distinct emotional states

Abstract: Although implicit tests of positive and negative affect exist, implicit measures of distinct emotional states are scarce. Three experiments examined whether a novel implicit emotion-assessment task, the rating of emotion expressed in abstract images, would reveal distinct emotional states. In Experiment 1, participants exposed to a sadness-inducing story inferred more sadness, and less happiness, in abstract images. In Experiment 2, an anger-provoking interaction increased anger ratings. In Experiment 3, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 41 publications
9
30
0
Order By: Relevance
“…One caveat to mention is that participants in the anger condition reported mixed feelings with a similar level of sadness as those in the sadness condition. Although somewhat dismaying, these findings are consistent with past research using the same anger induction method (e.g., Gross & Levenson, 1995;Hewig et al, 2005) and could be explained by limitations of self-reports to distinguish between similarly valenced emotions (e.g., Abercrombie et al, 2005;Bartoszek & Cervone, 2017;Polivy, 1981;Quirin et al, 2009). Further, as suggested by some authors (e.g., Fayant et al, 2017;Sigall & Mills, 1998), when the results on the main dependent variable are in line with predictions (as is the case here where conformity systematically varies depending on theoretical appraisal tendencies of each target emotion), and there is no plausible alternative explanation, manipulation checks should be given a diminishing role in explaining the findings.…”
Section: Discussionsupporting
confidence: 89%
“…One caveat to mention is that participants in the anger condition reported mixed feelings with a similar level of sadness as those in the sadness condition. Although somewhat dismaying, these findings are consistent with past research using the same anger induction method (e.g., Gross & Levenson, 1995;Hewig et al, 2005) and could be explained by limitations of self-reports to distinguish between similarly valenced emotions (e.g., Abercrombie et al, 2005;Bartoszek & Cervone, 2017;Polivy, 1981;Quirin et al, 2009). Further, as suggested by some authors (e.g., Fayant et al, 2017;Sigall & Mills, 1998), when the results on the main dependent variable are in line with predictions (as is the case here where conformity systematically varies depending on theoretical appraisal tendencies of each target emotion), and there is no plausible alternative explanation, manipulation checks should be given a diminishing role in explaining the findings.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, although no participants expressed any suspicion about the aim of the study, there is no guarantee that they did not alter their responses to conform to social demands (e.g., were reluctant to admit that they felt positive affect after they saw the sad sender). Future research might be supplemented with other measures that go beyond emotional expressions but are less biased than self-reports (e.g., implicit measures of affect; Bartoszek & Cervone, 2016; Quirin, Kazen, & Kuhl, 2009). Fourth, the conclusions concerning the role of the social context are limited because they are based on the indirect comparison of participants’ reactions to two different targets: the videotaped man and their partner sitting in the adjacent room.…”
Section: Discussionmentioning
confidence: 99%
“…The most promising techniques may well be emotional adaptations of implicit affect (the IPANAT; Quirin, Kazén, & Kuhl, 2009) and of well-established social cognition tests of implicit evaluation (the Implicit Association Test [IAT], Egloff, Weck, & Schmukle, 2008; the Affect Misattribution Procedure [AMP], Payne, Cheng, Govorun, & Stewart, 2005; and stem completion, DeWall & Baumeister, 2007; Gawronski & De Houwer, 2014). One possible avenue is suggested by work from Bartoszek and Cervone (2016), who have shown that ratings of emotion expressed in abstract paintings reflect raters’ current acutely induced or chronically activated emotional state (at least sadness, joy, and fear). Another direction worth exploring is implied by embodiment approaches, the idea that emotions are for action.…”
Section: Group-based Emotions: the Next Decadementioning
confidence: 99%